The Role of AIESEC in Implementing SDGS No. 4 Through Global Volunteers in the Suphanburi, Thailand - Rahmad Eko Wiranto; Shannaz Mutiara Deniar; Bhornpat Pornsuratana (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
This research examines the role of AIESEC as an international organization in facilitating the implementation of SDGs through Global Volunteers in Suphanburi, Thailand. The SDGs' implementation affects getting involved and contributing actively to making the world a better place, especially regarding